2023
DOI: 10.25122/jml-2022-0168
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of comorbid diseases in patients after COVID-19

Umida Kamilova,
Akbal Ermekbaeva,
Nuriddin Nuritdinov
et al.

Abstract: The COVID-19 pandemic has highlighted the potential impact of this disease on cardiovascular morbidity and mortality. Patients with established cardiovascular (CV) disease are at increased risk of severe infection and hospital-acquired adverse outcomes. This study aimed to investigate the prevalence and characteristics of comorbidities in COVID-19 patients. We analyzed data from 220 patients who previously contracted COVID-19. Statistical analysis was performed using SPSS software. The average age of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Comparative studies have shown the potential to investigate the immunological status across various groups of COVID-19 patients, including those with differing disease severities and even asymptomatic or healthy individuals. 28 In a study conducted by Wiech et al, they examined a group of patients who experienced a severe course of coronavirus infection. 29 Their findings revealed a significant increase in the number of final effector cells CD8+ CD57+ six months after infection, accompanied by a substantial reduction in the population of naïve T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have shown the potential to investigate the immunological status across various groups of COVID-19 patients, including those with differing disease severities and even asymptomatic or healthy individuals. 28 In a study conducted by Wiech et al, they examined a group of patients who experienced a severe course of coronavirus infection. 29 Their findings revealed a significant increase in the number of final effector cells CD8+ CD57+ six months after infection, accompanied by a substantial reduction in the population of naïve T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to assess the clinical course of the disease, complications, clinical and functional features of comorbid conditions in patients with COVID-19 are focused on identifying new aspects and early signs of etiopathogenesis by studying specific biomarkers and molecular genetic factors; scientific research is being carried out to develop a methodology for early detection and prediction of the risk of complications of the disease [6,7,13]. Direct and indirect damage to SARS-CoV-2 endothelial cells in patients with COVID-19 increases the activity of the reninangiotensin-aldosterone system (RAAS), which increases the risk of worsening the course of the disease and developing an unfavorable prognosis [8,9,11]. In a multicenter cohort study, elevated levels of endothelial dysfunction biomarkers, RAAS hormones, in patients with COVID-19 were associated with an increased risk of death and poor prognosis [10,12].…”
Section: Introductionmentioning
confidence: 99%